Emerging practices in onboarding programs for PAs: Strategies for onboarding. Issue 1 (January 2021) - Anglin, Lorraine; Sanchez, Mara; Butterfield, Rita; Rana, Rachel; Everett, Christine M.; Morgan, Perri
ABSTRACT: Objective: This is the final article in a series that examines the role of onboarding programs for new physician assistants (PAs) and NPs. On-the-job learning is highly relevant for this workforce. Here we examine the strategies organizations use to impart information and skills in onboarding programs. Methods: In 2018, we interviewed 13 administrators of onboarding programs. Interviews were transcribed and analyzed for themes by a team of researchers, with feedback from interviewees. Results: Seven strategies were identified and are described in this article: Clinical mentoring, personal and professional mentoring, meeting with/shadowing other professionals, checking in by administrators, delivering didactic content, tailoring content or ramp-up, and assessing/ensuring competency. Conclusions: This article describes commonly used strategies in onboarding programs for PAs and NPs and can provide guidance to those designing their own onboarding programs. The programs we examined relied heavily on mentoring and other strategies appropriate for adult learners. Future work should evaluate the effectiveness of onboarding programs.